2022
DOI: 10.1002/open.202200092
|View full text |Cite
|
Sign up to set email alerts
|

Potential Building Blocks for 1,4‐Dihydro‐N‐heteroacenes

Abstract: Studies have been performed aimed at the synthesis of N‐heteroacenes via substitution reactions of 4,5‐difluoro‐1,2‐dinitrobenzene with a diamine. The fluorine atoms are displaced first, followed by an activated nitro group. Two intermediates have been characterised by X‐ray single‐crystal structure determinations. Their intermolecular interactions were examined by Hirshfeld surfaces to assess their suitability for organic molecular electronics. The high reactivity of the phenazine, which is prone to oxidise a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 52 publications
(85 reference statements)
0
6
0
Order By: Relevance
“…Our studies so far making phenazines have shown that the fluorine atoms displace in preference to a nitro group in EtOH. 6,7 Exploratory studies on reactions of compound 7 in dimethylformamide (DMF) with nucleophiles are reported here. DMF might be a better dipolar aprotic solvent for substitution reactions because it does not hydrogen bond to the nucleophile in the same manner that it is a better solvent than methanol (MeOH) for certain nucleophilic substitution reactions.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our studies so far making phenazines have shown that the fluorine atoms displace in preference to a nitro group in EtOH. 6,7 Exploratory studies on reactions of compound 7 in dimethylformamide (DMF) with nucleophiles are reported here. DMF might be a better dipolar aprotic solvent for substitution reactions because it does not hydrogen bond to the nucleophile in the same manner that it is a better solvent than methanol (MeOH) for certain nucleophilic substitution reactions.…”
Section: Discussionmentioning
confidence: 99%
“…These studies are helpful for our ongoing work on an iterative approach to NOS-heteroacenes using 4,5-difluoro-1,2-dinitrobenzene 7 as a building block. 6,7…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations